Ornamental shrubbery - Wheeler, Mark (My University, 1897)
Introduction: A knowledge of ornamental plants is desired by all. If we see a beautiful tree or a pretty flower, our first thought is, What is it? and our next action is to go to the plant, examine its foliage, smell of its flowers, study their structure, and in every way impress upon the mind all the characteristics of the plant. If we are only a casual observer out interest in the plant will end there; but if we have become a student of “ornamental planting” we not only examine the plant with regard to its appearance at that particular time, but study its other relations. If our mind runs into technical lines we examine it for botanical characteristics which will distinguish it from the surrounding plants or we find in it peculiar features in its relations to the soil and climate, or we may notice variations as to the time of its coming into leaf or into bloom. If our mind is given to dwelling upon the aesthetic we will see in every plant a harmony which appeals to man’s finer nature.
Citation: Wheeler, Mark. Ornamental shrubbery. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Horticulture; Landscaping; Ornamental plants; Theses; Manuscripts (documents)